Strategi Pemeliharaan Sarana dan Prasarana Sekolah Berbasis Lingkungan Berkelanjutan - Sabrifha, Eli (Jurnal Kependidikan, 2025)
This study aims to uncover the needs of educational facilities and infrastructure, identify the obstacles faced, and formulate sustainable and practical maintenance strategies. A qualitative approach with a literature study method was chosen as the research method. Various sources were referred to, including journals, books, articles, theses, theses, and the latest information from social media. The data collection process was carried out through analysis and reading of relevant information. Data analysis used an interactive analytical model, including data condensation, data presentation, and drawing conclusions. The results of the study indicate that effective planning and maintenance of facilities and infrastructure are the keys to improving the quality of education. Adequate and well-maintained facilities will create a conducive learning environment and support an effective learning process. To achieve optimal management, a comprehensive strategy and collaboration between various parties are needed. The challenges faced are quite complex, ranging from limited funds to a lack of awareness of the importance of sustainable maintenance. Therefore, careful planning and solid cooperation are needed to overcome these obstacles. It is hoped that the implementation of the right strategy can provide maximum support for teaching and learning activities, creating a better and more sustainable educational environment. The success of this effort will have a positive impact on the overall quality of education.